2015
DOI: 10.1016/j.neuro.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos and malathion have opposite effects on behaviors and brain size that are not correlated to changes in AChE activity

Abstract: Organophosphates, a type of neurotoxicant pesticide, are used globally for the treatment of pests on croplands and are therefore found in a large number of conventional foods. These pesticides are harmful and potentially deadly if ingested or inhaled in large quantities by causing a significant reduction in acetylcholinesterase (AChE) activity in the central and peripheral nervous system. However, much less is known about the effects of exposure to small quantities of the pesticides on neural systems and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 42 publications
(59 reference statements)
5
43
0
Order By: Relevance
“…Similar decreases in locomotion or PMR behaviors have been reported for larval zebrafish following exposure to DZN (Scheil et al, 2009; Yen et al, 2011) and other organophosphate insecticides across a variety of ages (Levin et al, 2004; Pérez et al, 2013; Richendrfer et al, 2012; Şişman, 2010; Tilton et al, 2011). However, this trend may not hold true for all cases, as previous work has indicated that specific types of behavioral responses may be compound specific among different organophosphates (Richendrfer and Creton, 2015). …”
Section: Discussionmentioning
confidence: 92%
“…Similar decreases in locomotion or PMR behaviors have been reported for larval zebrafish following exposure to DZN (Scheil et al, 2009; Yen et al, 2011) and other organophosphate insecticides across a variety of ages (Levin et al, 2004; Pérez et al, 2013; Richendrfer et al, 2012; Şişman, 2010; Tilton et al, 2011). However, this trend may not hold true for all cases, as previous work has indicated that specific types of behavioral responses may be compound specific among different organophosphates (Richendrfer and Creton, 2015). …”
Section: Discussionmentioning
confidence: 92%
“…Other effects in larvae include decreased dopamine and serotonin levels and increased transmitter turnover (Eddins and others 2010), decreased swimming activity (Jin and others 2015; Levin and others 2004; Yen and others 2011) and decreased habituation of swimming over time (Levin and others 2004). Reduced anxiety-related behavior (thigmotaxis) by CPF is unrelated to changes in AChE activity (Richendrfer and Creton 2015; Richendrfer and others 2012). The assessment of adult fish indicates reduced dopamine levels, spatial learning impairments, increased swimming activity and increased sensorimotor response (startle response) (Eddins and others 2010; Levin and others 2003; Sledge and others 2011).…”
Section: Organophosphates (Ops)mentioning
confidence: 99%
“…Chlorpyrifos bond with cholinesterase by covalent [7,8] resulting in the accumulation of acetylcholine in the nervous system [8,9]. They causes irreversible inhibition of AChE, which leads to neuronal overstimulation and death [9].…”
Section: Introductionmentioning
confidence: 99%
“…Their tests show that 300 nM (≈ 0.1 mg/L) Chlorpyrifos exposure over 5 days inhibited AChE activity by over 80%. Richendrfer et al [8] observed that Larvae treated with 0.1 mM (≈ 35.0mg/L) Chlorpyrifos had decreased more than 30% of levels of AChE. Recent researches showed that Chlorpyrifos could destroy oxygen free radical balance and form oxidative stress [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation